2011
DOI: 10.1093/infdis/jir180
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Durability of Immune Responses After Hepatitis A Vaccination Among HIV-Infected Adults

Abstract: Most adults with well-controlled HIV infections had durable seropositive responses up to 6-10 years after HAV vaccination. Suppressed HIV RNA levels are associated with durable HAV responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 41 publications
2
54
1
2
Order By: Relevance
“…In the same study, the annual waning of antibodies after the second dose of vaccine was estimated to be 15%. Recently, CrumCianflone et al reported data about the long-term immunity to HAV among 130 HIV-infected adults (7). After an initial seroconversion rate of 89%, 90% (104 of 116; 95% CI, 83% to 95%) of responders remained seropositive at 3 years and 85% (63 of 74; 95% CI, 75% to 92%) at 6 to 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the annual waning of antibodies after the second dose of vaccine was estimated to be 15%. Recently, CrumCianflone et al reported data about the long-term immunity to HAV among 130 HIV-infected adults (7). After an initial seroconversion rate of 89%, 90% (104 of 116; 95% CI, 83% to 95%) of responders remained seropositive at 3 years and 85% (63 of 74; 95% CI, 75% to 92%) at 6 to 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines also recommend HAV vaccination as an important preventive strategy for HIV-infected MSMs, IDUs and persons with chronic liver disease or co-infected with hepatitis B and/or C. 16 Studies also reveal that HAV vaccination could induce durable seropositive responses up to 6-10 years among HIV-infected adults and could induce high immune response in HIVinfected children aged 2-16 years. 17,18 Hepatitis B virus is one of the major causes of chronic liver disease in Taiwan. 18 of 23 (78.3%) tested adolescents in our study were born after July 1984 when the nationwide Hepatitis B Vaccine (HBV) vaccination program was launched.…”
Section: Discussionmentioning
confidence: 99%
“…56 The duration of protection is linked to the control of HIV virus replication at the time of vaccination. 57 As in the general population, vaccination against HAV is recommended in non immune (negative for anti-HAV IgG) HIV-infected patients in certain situations, including HCV and/or HBV co infection, chronic liver disease, and patients at risk of exposure (MSM, intravenous drug addicts, travelers in endemic areas). The administration schedule comprises at least 2 vaccine doses.…”
Section: Hepatitis a Vaccinementioning
confidence: 99%